Problem-Solving Skills of Students in Electrochemistry Using a Flipped Classroom Model - Necor, Dexter (JPAIR Institutional Research, 2021)
The pedagogical practice of the flipped classroom model (FCM) was undertaken to determine the students' problem-solving skills in electrochemistry. A quasi-experimental design was used in this study using two contrasted groups, experimental group (flipped classroom) and control group (conventional classroom). The freshmen civil engineering students were the respondents of the study. Five factors of problem-solving skills were used as a scheme interpretation of student's answers such as (a) Problem Comprehension; (b) Understanding Relationships Among Chemical Concepts; (c) Understanding Associated Chemical Concepts (d) Applying Appropriate Problem-Solving Strategies; and (e) Using Appropriate Mathematics.    Results revealed that student’s under the flipped class was of better problem comprehension and can relate chemical concepts to the problem than the conventional class. Most of the students can do mathematical calculations in both groups but failed to explain the underlying concepts. Many students have many misconception statements on the oxidizing-reducing agents and the flow of electrons in the anode to cathode. The spontaneity of the cell was also the least understood. Nonetheless, many students can solve the standard and non-standard Ecell potential and Gibbs free-energy (?Gº). Ergo, the flipped classroom teaching is a successful teaching approach in enhancing the problem-solving skills in learning electrochemistry.
Keywords: Education; problem-solving skills; electrochemistry; flipped classroom model; quasi-experimental design; Philippines